The synergistic effects of transformational leadership and communication competence on organizational culture in nonprofit organizations - Novianty Elizabeth Ayuna; Abdorrakhman Gintings (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study examined the influence of transformational leadership and communication competence on organizational culture in a nonprofit organization. The problem addressed was the lack of clarity regarding how these two factors interact to shape culture in the Indonesian context. A quantitative survey with an ex-post facto design was conducted involving all 36 employees of a foundation. Data were collected through a structured Likert-scale questionnaire, tested for validity and reliability, and analyzed using regression techniques. The results indicated that transformational leadership significantly influenced organizational culture (R² = 0.653), while communication competence also had a significant effect (R² = 0.476). Combined, both factors explained 87.1% of the variance, demonstrating a strong synergistic effect. The study concluded that strengthening leadership and communication simultaneously is essential for developing adaptive and sustainable organizational cultures in nonprofit institutions.